2017
DOI: 10.1002/2017gl073642
|View full text |Cite
|
Sign up to set email alerts
|

L band microwave remote sensing and land data assimilation improve the representation of prestorm soil moisture conditions for hydrologic forecasting

Abstract: Recent advances in remote sensing and land data assimilation purport to improve the quality of antecedent soil moisture information available for operational hydrologic forecasting. We objectively validate this claim by calculating the strength of the relationship between storm‐scale runoff ratio (i.e., total streamflow divided by total rainfall accumulation in depth units) and prestorm surface soil moisture estimates from a range of surface soil moisture data products. Results demonstrate that both satellite‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 25 publications
5
76
0
Order By: Relevance
“…Following Crow et al (2005Crow et al ( , 2017, the Spearman rank correlation (R) between antecedent soil moisture and the event runoff coefficient is sampled across all available storm event periods within each basin between 31 March 2015 and 31 May 2017. Rank correlation is applied to minimize the confounding effect of potential nonlinearity in the relationship between antecedent soil moisture and event runoff coefficient.…”
Section: Storm Event Definition and Rank Correlation Metricmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Crow et al (2005Crow et al ( , 2017, the Spearman rank correlation (R) between antecedent soil moisture and the event runoff coefficient is sampled across all available storm event periods within each basin between 31 March 2015 and 31 May 2017. Rank correlation is applied to minimize the confounding effect of potential nonlinearity in the relationship between antecedent soil moisture and event runoff coefficient.…”
Section: Storm Event Definition and Rank Correlation Metricmentioning
confidence: 99%
“…Sampling error bars for R in individual basins are estimated using a 5,000-member boot-strapping approach (where individual storm events are randomly sampled with replacement to preserve the underlying storm event sample size) and then combined to estimate uncertainty in R. Based on the auto-correlation analysis in Crow et al (2017), the 16 basins in Figure 1 are assumed to contain 7.4 spatially independent samples. This adjusted sample size is used to calculate the expected reduction in sampling uncertainty associated with averaging across all basins.…”
Section: Uncertainty Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Crow et al (2017) found that, among a range of competing soil moisture products, SMAP L4 surface soil moisture estimates provide the highest correlation with independently observed streamflow data for 16 basins in the south-central United States. For example, Crow et al (2017) found that, among a range of competing soil moisture products, SMAP L4 surface soil moisture estimates provide the highest correlation with independently observed streamflow data for 16 basins in the south-central United States.…”
Section: Introductionmentioning
confidence: 99%
“…One promising approach to improving SM estimation in turn improving rainfall-runoff modeling is to integrate the observed SM into the hydrological modeling process using data assimilation (DA) techniques [11][12][13][14][15][16]. In general, the SM data for integration can be obtained from field measurements and satellite observations.…”
Section: Introductionmentioning
confidence: 99%